Legal Study of the Failure of Mediators in Resolving Disputes on the Division of Collective Property After Divorce (Study in Medan Religious Courts) - Pulungan, Nita Nilan Sry Rezki; Andriati, Syarifah Lisa (Universitas Sumatera Utara, 2024)
In Article 1 of the Marriage Law, marriage reflects the spiritual and physical bond between a man and a woman with the aim of forming a happy and lasting family based on faith in the Almighty God. In legally valid marriages, the role of assets is crucial in building a household, both as individual and joint assets. Issues related to marital assets often arise, affecting the well-being and comfort within the marriage. Reasons for divorce include invalid marriages, domestic violence, neglect of responsibilities, and prolonged disputes. When both parties seek divorce, mediation is utilized as a means to resolve conflicts, guided by a mediator seeking resolution options. This study identifies factors contributing to the failure of mediation in resolving disputes over joint property. These factors include parties' knowledge, absence, cultural and character differences, reluctance to compromise, prolonged and complex conflicts, ill intentions, external influences, lack of understanding of rights and obligations, and materialistic tendencies. The success of mediation in the Medan Religious Courts depends on the mediator's ability, derived from knowledge, education, training, and experience, which serves as a tool to effectively assist parties in resolving their disputes.